The SAGES Manual A Practical Guide to Bariatric Surgery - Nguyen, Ninh T.; DeMaria, Eric; Ikramuddin, Sayeed; Hutter, Matthew M. (Springer New York : Imprint: Springer, 2008)
Obesity is an epidemic in most developed countries. Bariatric surgery is growing at an exponential rate, with more than 140,000 bariatric operations performed in the U.S. yearly. In keeping with the other manuals in the series, The SAGES Manual of Bariatric Surgery presents a practical "how to" approach to minimally invasive bariatric surgery. The patient care needs are addressed in introductory chapters dealing with the rationale for surgery; overview of operations; preoperative assessment; psychological evaluation; and postoperative follow up, including behavioral issues and dietary guidelines. The editors then address the practicalities of setting up a bariatric program and both case and practice management. The subsequent sections cover techniques (Roux-en-Y, Lap-Band, malabsorptive operations and staged procedures), outcomes (including adolescent cases), and possible complications (leaks, bleeding, obstruction, stomas). These procedural chapters allow the reader to make decisions based on the evidence and best practices. Finally, the Manual wraps up with guidelines and accreditation requirements in bariatric surgery. This section stresses the importance of continuing education and consistent certifications.